Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2011)
with coexistent macular hole in the era of internal limiting membrane peeling Am J Ophthalmology 2011 Oral mucosal graft with amniotic membrane transplantation for total limbal stem cell deficiency Liu J, Sheha H, Fu Y , Giegengack M, Tseng SCG Am J Ophthalmology 2011; 152: 739-47. Comparison of macular thickness measured by optical coherence tomography after deep anterior lamellar keratoplasty and penetrating keratoplasty Am J Ophthalmology 2011; 152: 756-61.